Genetic parameters of some yield and yield contributing traits in silkworm, Bombyx mori L. - Reza, AMS; Rahman, SM (University Journal of Zoology, Rajshahi University, 2007)
Key words: Silkworm; variability; heritability; genetic advance Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 55-58